Comparative analysis of greenhouse emissions based on life cycle assessment of alternative fuels for transportation sector - A systematic literature review (2023)
ABSTRACT : The shift towards sustainable energy sources has become a primary subject of discussion when considering the future of energy. It is crucial to move from traditional to nonconventional and sustainable sources of energy, given the depletion of fossil fuels and growing environmental concerns about the rising concentration of GHG in the atmosphere. This phenomenon causes the Earth's average temperature to increase, which can result in significant climate changes. Although Colombia only contributes to approximately 0.37% of global GHG emissions [1], it is largely affected by climate change, and is signatory of the Paris Agreement in 2015. Among the most outstanding and relevant goals proposed, is reduction carbon dioxide emissions by 51% and to achieve carbon neutrality by 2050. In order to achieve carbon neutrality by 2050, decarbonization of the transport sector is imperative, given its strong dependence on fossil energy sources. Policies are needed to accelerate and promote the establishment of infrastructure to support zero-emissions vehicles and the incorporation of low carbon fuels that are critical to decarbonizing aviation, shipping, and heavy-duty road freight. The ultimate solution to decarbonize the transport sector is to replace fossil fuels with CO2-lean energy sources. This requires identifying and supporting technologies that can deliver significant reductions in GHG emissions over the entire life cycle. The National Energy Plan PEN 2020-2050 outlines a long-term vision for Colombia's energy sector and explores potential ways to achieve it. The plan acknowledges that the transportation sector will play a significant role in the energy transition, where GHG mitigation can be achieved through the adoption of improved technologies, vehicle electrification, and the use of hydrogen and other advanced biofuels. While alternative fuels are not expected to be the primary focus of the energy transition, it is becoming increasingly clear that they will need to be part of the strategy. Studies have shown that next-generation renewable fuels offer a transition path towards low carbon emissions for the transportation sector. This study conducts a systematic literature review by collecting relevant studies related to the life cycle analysis of low carbon fuels intended for the transportation sector. The goal is to assess the potential of various alternative fuels for decarbonization. The study evaluates the life cycle GHG emissions and energy consumption considering fuel characteristics such as: raw material, production pathways, utilization technologies, energy efficiency and environmental performance. Finally, a meta-analysis is conducted to compare the GHG abatement potential of all low carbon fuels and their pathways with fossil energy sources.